Exploring Peri-Implantitis Risk-Factors: A Cross-Sectional Study - Simina Angela Lăcrimioara Iușan; Ondine Patricia Lucaciu; Nausica Bianca Petrescu; Ioana Codruța Mirică; Dan-Alexandru Toc; Silviu Albu; Carmen Costache (Dentistry Journal)
Background/Objectives: With the increasing use of dental implants in edentulous patients and the high prevalence of peri-implantitis, understanding its microbial and risk factors is crucial. This study investigated Romanian patients from two private dental clinics in Cluj-Napoca, Romania, diagnosed with peri-implantitis, focusing on identifying the predominant bacterial species at affected sites compared with healthy implant sites. Additionally, we examined the impact of factors such as smoking, gender, age, and prosthetic restoration type on disease prevalence. Methods: This cross-sectional study, conducted between January 2023 and December 2024, included randomly selected patients who met the predefined inclusion and exclusion criteria. We enrolled 22 patients and 50 implants in the study. Data collected from medical records, clinical evaluations, and microbiological assessments were subsequently entered into a computerized database. Clinical data were analyzed using Social Science Statistics software(Jeremy Staangroom 2018). Bacterial samples were assessed, incubated, and subsequently identified using the Vitek 2 Compact System (BioMérieux, Marcy—l’ Étoile, France). Results: Peri-implantitis incidence was found to be independent of gender, more prevalent in the mandible, and equally affected smokers and non-smokers. The disease involves a complex polymicrobial infection, with pathogenic bacteria triggering the condition and opportunistic bacteria sustaining it. Conclusions: Peri-implantitis is a complex polymicrobial infection that arises from the interaction of strict pathogenic bacteria and opportunistic bacteria. Peri-implantitis results from intricate interactions of local, systemic, and microbial factors. Identifying its causes is essential for developing effective treatments, with future research emphasizing the role of opportunistic bacteria in disease progression.